Effectual components of Polygonum ciliinerve protects against Staphylococcus aureus infection with immunomodulatory functions in C57BL/6 mice - Cao,Lanxiu (2018)
Abstract Purpose: To investigate the efficacy and mechanisms of root tuber of Polygonum ciliinerve (Nakai) ohwi (rPC) which has been used to treat bacterial infection in traditional Chinese medicine. Methods: With the mouse model of Staphylococcus aureus (S. aureus) pneumonia, the phenotype of rPC treated mice, including body weight, mortality, lung slices and bacterial burden were evaluated. Furthermore, inflammatory factors in bronchoalveolar lavage (BAL) were determined by ELISA and the distribution of T cells in lung was assessed by immunofluorescence assay. Results: rPC treatment could dose-dependently reduce weight loss and mortality in S. aureus-infected mice. Upon 10 mg/ml rPC treatment, S. aureus-infected mice showed about 8 grams increase in body weight (P<0.001) and 50% enhancement in mortality. The integrity of lung tissue and bacterial burden were also improved by rPC treatment. Moreover, rPC was found to modulate the immune response in infection. Conclusion: rPC has therapeutic potential for S. aureus infections and pneumonia with immunomodulatory functions.